2013
DOI: 10.5897/ajfs12.111
|View full text |Cite
|
Sign up to set email alerts
|

Extending the use of an underutilised tuber I: Physicochemical and pasting properties of cocoyam (Xanthosoma sagittifolium) flour and its suitability for making biscuits

Abstract: Cocoyam is one of the important root food crops especially among the low income earners in Nigeria. However, the utilisation options of cocoyam are mainly limited to direct consumption as whole boiled or pounded tuber only, thus making it an underutilised crop. Physicochemical and pasting properties of cocoyam flour, its suitability and acceptability in biscuit making were determined. Red and white cocoyam varieties were processed into flour by sun-drying method. The physicochemical and pasting properties were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(15 reference statements)
1
4
2
Order By: Relevance
“…Pasting temperature of the cocoyam flour samples investigated was higher than those reported by Oladeji et al (2013). In the study of Ejoh et al (2013), pasting temperatures ranged from 61.73 ± 0.04 to 61.95 ± 0.42°C and are lower than the values obtained in this study. Since fermentation and storage at 45°C for 4 weeks resulted into sample with the highest pasting temperature, it suggests that the resultant flour from this process will cook at a higher temperature than other samples and hence it require higher energy and will cook for a longer period than the other samples.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Pasting temperature of the cocoyam flour samples investigated was higher than those reported by Oladeji et al (2013). In the study of Ejoh et al (2013), pasting temperatures ranged from 61.73 ± 0.04 to 61.95 ± 0.42°C and are lower than the values obtained in this study. Since fermentation and storage at 45°C for 4 weeks resulted into sample with the highest pasting temperature, it suggests that the resultant flour from this process will cook at a higher temperature than other samples and hence it require higher energy and will cook for a longer period than the other samples.…”
Section: Discussioncontrasting
confidence: 89%
“…Pasting characteristics of flour are of importance in food processing because they influence the texture, stability, and digestibility of starchy foods and, thus, determine the application and use of the flour in various food products. The peak viscosity values obtained in this study is relatively high compared to the range of values reported for cocoyam flour 161.80-267.58 RVU by Ejoh et al (2013). The lowest value was obtained in the fermented sample stored at 45°C for 2 weeks and the highest in the parboiled sample stored at 25°C for 6 weeks.…”
Section: Discussioncontrasting
confidence: 51%
“…The observed peaks could be ascribed to the stretching vibrations of O–H, and differences in peaks could be linked to variations of moisture content of FM flours caused by fermentation, as reported by Mudau et al [ 70 ]. Moisture content has been reported to be responsible for the peaks in O–H stretch region [ 28 , 83 ]. Higher peak values observed in fermented flours suggest the presence of more alcohol produced during fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…They affect the sensory and textural properties, as well as the shelf-life, of food products [ 27 ]. Pasting properties determine the suitability of flours for baking applications [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to Ganança et al (2015) and Mabhaudhi et al (2013), the response of different cocoyam cultivars to drought is variable and therefore choice of appropriate cultivars is important for production under climate change. There is need for the drought tolerant varieties to have comparable preparatory qualities such as starch granule sizes, amylose content, viscosity, pasting time, water absorption capacity, gelling point, foam capacity, bulk density and swelling power (Falade and Okafor 2013;Isibhakhomen et al 2013;Kaushal et al 2012) and nutritional qualities such as protein, energy, calcium, potassium and other micronutrients (Akwee et al 2015;Darkwa and Darkwa 2013). The changes in production and preparatory characteristics are of special interest given the gender bias of neglected and underutilized crops such as cocoyam that are almost entirely a preserve of women.…”
Section: Discussionmentioning
confidence: 99%